The Role of the Academy and HRD in the Changing of the Guard. Issue 1 (February 2020) - Rosenbusch, Katherine; Morrison, Emily
The Problem: Life for faculty members is becoming more complex and stressful due to the rate of change and the ever-increasing demands being placed on them: publish in top journals, apply for funding, teach and support more students, integrate new technology into classes, serve on committees, and contribute to your discipline and professional association. Current systems, policies, and practices within higher education often fail to recognize the unique contributions of faculty members, especially those who might not reflect the traditional perspectives that have been put in place for decades. Rather, there remains a strongly guarded tradition of what is valued and rewarded within higher education. Hence, higher education needs to transform its organizational culture, valuing individual contributions, meeting workforce demands, and ensuring the health of the education system and society. The Solution: The field of human resource development (HRD) with its interdisciplinary roots and expertise in learning, leadership, organizational change, and culture is uniquely poised to not only inform this conversation, but also to critique and contribute to the transformation of faculty work and associated expectations. This Issue addresses and identifies where changes are needed at the individual, organizational, and societal levels to transform the role of faculty members so that it is better aligned with the current environment and context of higher education. The Stakeholders: Scholars, practitioners, administrators, and community who recognize that the health of the broader community is affected by the quality of higher education and, in particular, faculty and the way that they teach and prepare students to be scholar-practitioners.